2001
DOI: 10.1038/labinvest.3780223
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Relevance of T1-S, an Oncogene-Inducible, Secreted Glycoprotein of the Immunoglobulin Superfamily, in Node-Negative Breast Cancer

Abstract: SUMMARY:Axillary lymph node-negative breast cancer patients have a low risk for disease recurrence, and the majority of these patients are cured by surgery alone. However, accurate identification of that 30% of node-negative patients who are at high-risk for relapse and who might therefore benefit from adjuvant systemic therapy has not been possible using traditional histomorphological and clinical prognostic factors alone. Identification of novel tumor-associated molecules may therefore provide a basis for a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…However, interestingly, two homozygous knockout mice spontaneously developed what appeared to be subcutaneous tumors on their neck and trunk and a third animal was found moribund due to unknown causes (not shown). Possibly relevant to these observations are previous findings that sST2 is correlated with progression of breast cancer [15] and that sST2 may modulate tumor cell activity in vitro [16].…”
Section: Introductionmentioning
confidence: 55%
“…However, interestingly, two homozygous knockout mice spontaneously developed what appeared to be subcutaneous tumors on their neck and trunk and a third animal was found moribund due to unknown causes (not shown). Possibly relevant to these observations are previous findings that sST2 is correlated with progression of breast cancer [15] and that sST2 may modulate tumor cell activity in vitro [16].…”
Section: Introductionmentioning
confidence: 55%
“…25 ST2 expression is increased in situ in breast cancer and is associated with reduced disease progression. 26 These findings suggest that confounding systemic inflammatory/immune diseases have the potential to complicate the predictive value of serum ST2 measurements in heart failure, although at the present time, asthma and some autoimmune diseases are the only diseases other than heart failure in which an increase in serum ST2 has been identified. We recently found that ST2 levels were acutely increased in the serum of patients 1 day after myocardial infarction, positively correlated with creatine kinase levels, and inversely correlated with ejection fraction.…”
Section: Discussionmentioning
confidence: 94%
“…Recent data on the expression of ST2, the human homologue to T1, in human breast cancers are somewhat conflicting, however. The secreted ST2‐S form was overexpressed in two‐thirds of patients with lymph node–negative breast cancers associated with a high to moderate level of differentiation of the tumors [56] and with a longer disease‐free survival period [57].…”
Section: Discussionmentioning
confidence: 99%